THE EFFECT OF NANOPARTICLES IN COMBATING PLANT DISEASES IN MAJOR CROPS: A REVIEW STUDY (International Journal of Food and Nutritional Sciences, 2022)
Plant diseases caused by pathogens are a major threat to global food security. Nanoparticles have been integrated into disease management strategies, serving as both bactericides/fungicides and nano-fertilizers to enhance plant health. With a warming climate, the demand for food production is increasing. Nanoparticles can help manage new disease challenges while reducing the need for active metals and other chemical inputs. Small sizes of the nanoparticles have the potential to target and directly attack virus particles, opening up new possibilities for controlling plant pathogens. Nanoparticles efficiently overcome bacterial, fungal, and other plant pathogens in major food crops. Various types of nanoparticles have been found to enhance crops' resistance to both biotic and abiotic stresses.